Universidades comunitárias e compromisso social emtempos de mercantilização da educação superior : "o dizer a sua palavra" na percepção de investigadores da educação - Salatino, Vialana Ester (My University, 2023)
This PhD thesis is about community colleges and their social commitment in times of commodification of higher education: "saying your word? in the perception of education researchers. To carry out this research, it was essential to address topics related to higher education and university, about the COVID-19 pandemic, about community colleges, about the social commitment of these universities, about universities in times of commercialization of education, understand the concept of community/communitas, on immunit"s and biopolitics that permeate this reality, to delve into the issue of neoliberalism and the psychic suffering caused by it, to deepen knowledge about commodification and the tendency to disaggregation, to approach the Freirean concept "saying your word", to give voice to education researchers and in Paulo Freire's conception to shed light on autonomy, freedom, the oppressor and the oppressed. With that, I aimed to develop horizons/guidelines for community colleges in the sense of overcoming the constraints imposed by the commodification scenario of higher education. The theoretical contributions of the chapters have as main authors: Chauí (2018, 2011,1999), Dardot; Laval (2019, 2016), Dejours (2015), Esposito (2017, 2009, 1998), Foucault (2008, 2010, 1999), Freire (1996, 1993, 1987, 1981, 1976), Laval (2020, 2019, 2018), McCowan (2018, 2015), Pegoraro (2013), Santos (2020, 2011, 2009, 2006, 1998), Safatle; Silva Junior; Dunker (2021), Schmidt (2018, 2011, 2010), Sguissardi (2018, 2015, 2011, 2002), Trevisol (2009) and Vannucchi (2011) that strengthen the understanding of the university, community colleges, neoliberalism, psychological suffering, education and commodification of higher education. The methodology chosen was narrative research based on Clandinin and Connelly (2011, 2000), with a qualitative approach, using interviews according to Lüdke and André (2018). 2009), the interviews were carried out by discursive textual analysis (DTA) according to Moraes; Galiazzi (2020, 2006), which made it possible to write the metatext of the thesis, as indicated by Galiazzi; Souza (2019). The thesis presents horizons/guidelines for community colleges in the sense of overcoming the constraints imposed by the commodification scenario of higher education, and shows the reality without illusions. I point out some paths to be urgently implemented, difficult and challenging, but they are possibilities, especially together, to outline a safer reality for the community system that makes it possible to maintain the social commitment attributed to these universities. Excellence in higher education, research and extension, with dignity and support from the community at large and governments, as it should have been from the beginning. I conclude by saying that a lot of work exists in order to follow the horizons/guidelines listed in the writing of the metatext of the thesis, where I understand how it is possible to seek a safer path, its possibilities and impossibilities, although it is challenging to put into practice, are battles to be won in parallel with each other. the others, in order to win the war against a mercantile education in the end. [resumo fornecido pelo autor]
Esta Tese de doutorado versa sobre as Universidades Comunitárias e Compromisso Social em tempos de mercantilização da educação superior: "o dizer a sua palavra" na percepção de investigadores da educação. Para a concretização desta pesquisa foi fundamental abordar temáticas referentes a educação superior e Universidade, sobre a pandemia de COVID-19, sobre Universidades Comunitárias, a respeito do Compromisso Social dessas Universidades, sobre Universidades em tempos de mercantilização da educação, compreender o conceito de comunidade/communitas, sobre immunitas e biopolítica que permeiam essa realidade, adentrar na questão do neoliberalismo e do sofrimento psíquico por ele causado, aprofundar o conhecimento sobre mercantilização e a tendência à desagregação, abordar do conceito freireano "o dizer a sua palavra", para dar voz aos investigadores da educação e na concepção de Paulo Freire trazer luz sobre autonomia, liberdade, opressor e oprimido. Com isso objetivei elaborar horizontes/diretrizes para as Universidades Comunitárias no sentido de superação das amarras impostas pelo cenário de mercantilização do ensino superior. Os aportes teóricos dos capítulos têm como principais autores: Chauí (2018, 2011,1999), Dardot; Laval (2019, 2016), Dejours (2015), Esposito (2017, 2009, 1998), Foucault (2008, 2010,1999), Freire (1996, 1993, 1987, 1981, 1976), Laval (2020, 2019, 2018), McCowan (2018, 2015), Pegoraro (2013), Santos (2020, 2011, 2009, 2006, 1998), Safatle; Silva Junior; Dunker (2021), Schmidt (2018, 2011, 2010), Sguissardi (2018, 2015, 2011, 2002), Trevisol (2009) e Vannucchi (2011) que fortalecem o entendimento sobre a Universidade, as Universidades Comunitárias, o neoliberalismo, sofrimento psíquico, educação e mercantilização da educação superior. A metodologia escolhida foi a de pesquisa narrativa baseada em Clandinin e Connelly (2011, 2000), com abordagem qualitativa, utilizando entrevistas conforme Lüdke e André (2018), as entrevistas foram realizadas com especialistas que permitiram ser identificados ou não de acordo com Flick (2009), a análise dos dados se deu por análise textual discursiva (ATD) de acordo com Moraes; Galiazzi (2020, 2006), o que possibilitou a escrita do metatexto da Tese como indicam Galiazzi; Sousa (2019). A Tese apresenta horizontes/diretrizes para as Universidades Comunitárias no sentido de superação das amarras impostas pelo cenário de mercantilização da educação superior, e mostra a realidade sem ilusões. Aponto alguns caminhos a serem urgentemente implantados, difíceis e desafiadores, mas são possibilidades, principalmente em conjunto, para o delinear de uma realidade mais segura para o sistema comunitário que viabiliza manter o compromisso social atribuído a essas Universidades. A excelência em educação superior, pesquisa e extensão, com dignidade e apoio da comunidade em geral e dos governos, como deveria ser desde o início. Concluo dizendo que muito trabalho existe no sentido de seguir horizontes/diretrizes elencadas na escrita do metatexto da Tese, onde compreendo como é possível buscar um caminho mais seguro, suas possibilidades e impossibilidades embora seja desafiador colocar em prática, são batalhas a serem vencidas em paralelo umas das outras, para ao final se vencer a guerra contra uma educação mercantil. [resumo fornecido pelo autor]
Keywords: Ensino superior; Universidades e faculdades comunitárias; Mercantilismo - Educação; College teaching; Community colleges; Mercantile system - Education